Phát huy giá trị văn hóa và con người Việt Nam trong thời kỳ đổi mới - Đinh, Thị Hằng (Dạy và học ngày nay, 2023)
The history of mankind in general and the history of the Vietnamese nation, in particular, have proven that culture has been associated with human life and the development of society. Culture is not only the driving force of socio-economic development but also an influential factor creating the sustainable progress of the country and the nation. During the revolutionary cause of national liberation, under the leadership of the Communist Party of Vietnam, Vietnamese cultural and human factors have always been promoted, generating gigantic strength to defeat all invaders, gain and protect national independence and territorial integrity of the Fatherland.